Jumlah eritrosit, hemoglobin dan hematokrit pada tikus (Rattus norvegicus) yang diberi seduhan kopi arabika (Coffea arabica) - Dewi, Lolita Sintia; Yulihastuti, Dwi Ariani; Wijana, I Made Sara; Narayani, Inna (Jurnal Biologi Udayana, 2023)
Arabica coffee ( Coffea arabica ) contains tannins and caffeine which will interfere with iron absorption and cause anemia. This study aims to determine the number of RBC (Red Blood Cell) or erythrocytes blood hemoglobin levels and the percentage of PCV (Packed Cell Volume) or hematocrit in rats ( Rattus norvegicus ) treated with arabica coffee brew ( Coffea arabica L). The method used is RAL (Completely Randomized Design) in 5 treatment groups and each group contains 5 rats. Group 1 as control by giving 3,6 mL of distilled water. Group 2 as the first treatment (P1) by giving 3,6mL of brewed coffee powder dose of 150mg/200gBB, group 3 as the second treatment (P2) by giving 3,6mL of brewed coffee powder dose of 310mg/200gBB, group 4 as the third treatment (P3) by giving 3.6mL of brewed coffee powder dose 630mg/200gBB and group 5 as the fourth treatment (P4) by giving 3,6mL of brewed coffee powder dose of 1,260mg/200gBB. The method of steeping coffee with oral gavage is using an oral sonde. Data were analyzed using Analysis of Variance (ANOVA). The results obtained in this study were that brewed arabica coffee ( Coffea arabica ) did not have a real effect on the number of erythrocytes, hematocrit percentage and hemoglobin levels in rats ( Rattus norvegicus ) because caffeine and tannin levels that act as iron inhibitors have been reduced due to high temperatures in the roasting process. Caffeine levels in coffee samples have not affected iron absorption. Iron reserves in the body are still in a normal state so that they do not affect the process of erythropoiesis.